2006
DOI: 10.1111/j.1083-6101.2001.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

E-mail Survey Response Rates: A Review

Abstract: Electronic mail (e‐mail) has been used to distribute surveys and collect data from online users for almost fifteen years. However, some have suggested that the use of e‐mail is becoming obsolete. This study analyzes response rates to e‐mail surveys undertaken since 1986 and examines five influences to response rates: the year the study was undertaken, the number of questions in the survey, the number of pre‐notification contacts, the number of follow‐up contacts and survey topic salience. Response rates to e‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

88
624
4
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 927 publications
(754 citation statements)
references
References 40 publications
88
624
4
16
Order By: Relevance
“…The cost involved was only $40 to keep the survey active for 2 months. The response rate we observed is comparable to reported response rates from other Web-based surveys of physicians and surveys involving neonatologists [7,15,36]. Response rates for physician surveys are on average more than 10% lower than those for nonphysician surveys and have declined during the past decade [3,11].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The cost involved was only $40 to keep the survey active for 2 months. The response rate we observed is comparable to reported response rates from other Web-based surveys of physicians and surveys involving neonatologists [7,15,36]. Response rates for physician surveys are on average more than 10% lower than those for nonphysician surveys and have declined during the past decade [3,11].…”
Section: Discussionsupporting
confidence: 77%
“…We selected a Web-based survey mode because of the ability for rapid response, much lower cost compared to postal mail, and reduction of data entry errors [7,36]. The cost involved was only $40 to keep the survey active for 2 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jobber and Saunders (1993) noted potential respondents in business-oriented studies were more sensitive to survey length than those in consumer studies. Sheehan (2001) however, concluded that there was no correlation between email questionnaire length and response rate. Schaefer and Dillman (1998) identified through a review of past studies that email surveys with a single contact had a response rate of 28.5%.…”
Section: Comparison Of Various Survey Research Methodsmentioning
confidence: 97%
“…Our survey to the 993 individuals that submitted at least one solution to IC resulted in 377 responses of which 320 were complete for our analysis thus yielding a relatively high response rate of 32.2% (Sheehan 2001). The 320 respondents represented 93 (56%) of the 166 broadcast problems during the study period.…”
Section: Survey Sample Characteristicsmentioning
confidence: 99%